A positive lead paste of high-temperature-resistant long-life lead-acid storage battery and a preparation method thereof
Patent Information
- Application Number
- CN202611346461.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对现有技术中铅酸蓄电池在60℃左右长期浮充时,正极板栅腐蚀加速、活性物质软化脱落,硫酸铅晶粒异常长大问题,导致的寿命快速衰减、难以满足长周期可靠运行需求问题
[0029]综上所述,本发明通过在正极铅膏中加入硫酸盐、掺锑二氧化锡、Ti4O7导电陶瓷粉,有效解决了现有技术中铅酸蓄电池在高温浮充情况下,因正极板栅腐蚀显著加速、活性物质软化脱落而导致的寿命衰减问题。并且电池的初始容量、内阻和循环一致性未产生负面影响,显著提高了铅酸蓄电池在高温工况下的浮充循环寿命与使用可靠性。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lead-acid battery technology, and specifically discloses a positive electrode paste for a high-temperature resistant, long-life lead-acid battery and its preparation method. Background Technology
[0002] Lead-acid batteries are widely used in communications, energy storage, and backup power supplies due to their advantages such as low cost, high safety, strong environmental adaptability, high recyclability, and maintenance-free operation. In these applications, battery packs typically need to be in a float charge state for extended periods, meaning they are supplemented with a small current at a constant voltage to replenish self-discharge losses and ensure a fully charged state for emergency power supply.
[0003] Currently, lead-acid batteries typically exhibit good float charge lifespan in environments around 20℃ to 25℃. However, when batteries are continuously subjected to high-temperature float charge environments of around 60℃, the corrosion rate of the positive electrode grid accelerates significantly with increasing temperature. Simultaneously, the positive electrode active material is prone to structural loosening, softening, pulverization, and shedding, leading to a gradual reduction in effective active material. Furthermore, high temperatures exacerbate battery self-discharge and sulfation processes, resulting in more pronounced formation and deposition of lead sulfate in localized areas. This can cause lead sulfate grains to gradually coarsen, leading to decreased utilization of active material and continuous capacity decay, thus shortening the battery's float charge lifespan and making it difficult to meet the requirements for long-term, stable operation under high-temperature conditions.
[0004] To extend battery float life, existing technologies mainly focus on improving the positive electrode lead paste formulation, active material structure, and preparation process. For example, rare earth elements are added to the lead paste to improve the stability of the active material; tin-containing components such as stannous sulfate are added to improve the interface between the grid and the active material and reduce the corrosion tendency of the positive electrode grid; carbon-based materials such as graphene, carbon nanotubes, and acetylene black are added to improve the internal electron transport path of the active material and alleviate local current concentration. However, under long-term float charging conditions at 60℃ and above, the positive electrode active material is exposed to the combined effects of high temperature, high oxidation potential, and acidic electrolyte, making it prone to multiple failure problems such as accelerated grid corrosion, decreased structural stability of the active material, decreased conductivity with long-term operation, and localized lead sulfate deposition and grain coarsening. Existing single or a few added components mainly target one of these failure mechanisms, making it difficult to simultaneously address the stability of the crystal phase and pore structure of the positive electrode active material, mechanical resistance to shedding, long-term conductivity stability, and grid corrosion resistance. Therefore, developing a positive electrode paste that can maintain a long lifespan at high temperatures is of great practical significance for the development of lead-acid batteries. Summary of the Invention
[0005] To address the problems in existing lead-acid batteries where prolonged float charging at around 60°C leads to accelerated corrosion of the positive electrode grid, softening and shedding of active materials, and abnormal growth of lead sulfate grains, resulting in rapid lifespan degradation and difficulty in meeting long-term reliable operation requirements, this invention provides a high-temperature resistant, long-life lead-acid battery positive electrode paste. This paste can increase the high-temperature float charging life of lead-acid batteries by more than 30%, while maintaining stable capacity, rate capability, and consistency, making it highly valuable for widespread application.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The first aspect of this invention provides a positive electrode paste for a high-temperature resistant, long-life lead-acid battery. The positive electrode paste, by weight, comprises: 90-120 parts lead powder, 8-12 parts sulfuric acid, 2-3.5 parts sulfate, 0.05-0.1 parts short fibers, 0.2-0.4 parts antimony-doped tin dioxide, 0.1-0.3 parts Ti4O7 conductive ceramic powder, and 9-13 parts deionized water. The sulfate includes tetrabasic lead sulfate and barium sulfate; the short fibers include organic small-molecule short fibers and high-silica short-cut fibers.
[0007] Compared to existing technologies, the positive electrode lead paste provided by this invention exhibits superior high-temperature float charging performance. Specifically, the tetrabasic lead sulfate, as a key crystalline phase in the positive electrode lead paste, can regulate the structure of the positive electrode active material during battery formation and subsequent charge-discharge cycles, thereby mitigating failure issues such as accelerated grid corrosion, softening and shedding of the active material, and abnormal growth of lead sulfate grains. In particular, during the curing and ripening process, tetrabasic lead sulfate, as a stable crystal phase inducing component, participates in the formation and growth of the basic lead sulfate crystalline phase along with other components such as lead oxide. This facilitates a more uniform grain distribution and pore structure, improves the interfacial contact between the grid and the active material, enhances the structural density and stability of the interfacial region, thereby reducing the tendency for localized corrosion at the grid interface, delaying the positive electrode grid corrosion process, and reducing early capacity decay caused by interface degradation between the grid and the active material. During the formation process, tetrabasic lead sulfate participates in the formation of lead dioxide active material. Through its pre-formed crystal phase and pore structure, it regulates the nucleation, growth, and particle bonding processes of lead dioxide, enabling the generated lead dioxide particles to form a stable, interconnected crystal structure, further constituting a well-continuous lead dioxide crystal network. This structure enhances the bonding strength between active material particles, reducing softening, mudding, and detachment of the active material under high-temperature float charging conditions. Furthermore, it reduces structural damage caused by phase transformation and volume changes during charging and discharging, resulting in a more uniform formation and reduction process of lead sulfate, thereby reducing the tendency for abnormal coarsening of localized lead sulfate grains.
[0008] Barium sulfate is chemically stable, insoluble in sulfuric acid electrolyte, and does not decompose under high oxidation potential at the positive electrode. It can be used as an inert structural regulating component, uniformly dispersed in the positive electrode active material, to control the pore structure and particle distribution of the active material layer. During curing, ripening, and formation, barium sulfate particles maintain appropriate spacing between active material particles, reducing the tendency for localized densification and agglomeration. This promotes a more uniform pore structure and pore size distribution, allowing the electrolyte to penetrate the active material more evenly, thus reducing the tendency for excessive densification and reaction concentration in localized areas. This reduces the risk of excessive concentration of lead sulfate formation during charging and discharging, and lowers the risk of abnormal coarsening of lead sulfate in localized areas. Furthermore, barium sulfate can synergistically interact with tetrabasic lead sulfate. Tetrabasic lead sulfate helps construct a stable crystal network for the positive electrode active material, while barium sulfate, as a stable inert particle dispersed within the active material, regulates particle arrangement and pore structure. Together with tetrabasic lead sulfate, they complement each other in controlling crystal phase structure and microscopic spatial structure, improving the structural stability of the active material layer and reducing active material shedding. Meanwhile, this stable structure can buffer and disperse the volume changes of active materials during charging and discharging, reducing the tendency of active material particle structure damage, softening, pulverization and shedding, thereby improving capacity retention, cycle stability and service life under high temperature float charging conditions.
[0009] High-silica short fibers possess excellent acid corrosion resistance and electrochemical stability. In cathode lead paste, they maintain structural integrity over a long period and act as a stable fiber reinforcement phase, uniformly distributed within the active material to form a fiber-reinforced structure. This enhances the crack resistance and structural stability of the active material layer, further strengthening its anti-detachment effect. During long-term battery cycling, the conversion between lead dioxide and lead sulfate, along with volume changes, continuously generates localized mechanical stress within the active material, leading to microcracks or areas of loose structure. High-silica short fibers, distributed between active material particles, can bridge these microcrack areas, hindering further crack propagation and particle displacement, thus reducing the degree of structural damage. Simultaneously, the structure formed by high-silica short fibers and tetrabasic lead sulfate is complementary. The high-silica short fibers provide flexible reinforcement, allowing the active material to maintain a suitable pore structure while possessing good mechanical integrity. This reduces cracking, softening, pulverization, and detachment caused by repeated expansion, contraction, and stress accumulation during long-term charge-discharge and high-temperature float charging, thereby improving the cycle stability and high-temperature float charging life of the cathode active material.
[0010] Antimony-doped tin dioxide (SOD) exhibits high electronic conductivity and strong chemical and electrochemical stability in the high oxidation potential of the cathode and in sulfuric acid electrolyte environments. Due to its resistance to dissolution and structural damage, it can serve as a stable conductive reinforcing phase, uniformly dispersed within the cathode active material. SOD can synergistically improve the electron transport path and conductivity uniformity within the active material by working in conjunction with the stable active material crystal structure regulated by tetrabasic lead sulfate. Specifically, SOD can be distributed between lead dioxide particles and in the vicinity of inert particles such as barium sulfate. By increasing the microscopic conductive contact between active material particles, it improves the continuity and uniformity of electron transport paths, reducing the localized electron transport limitation caused by the presence of low-conductivity components such as barium sulfate. This results in more uniform electrochemical reactions in different regions during charge and discharge, reducing localized polarization and reaction concentration. Consequently, it can mitigate the structural degradation of the active material caused by localized reaction concentration and increased polarization, reducing the tendency for softening, pulverization, and shedding of the active material during high-temperature float charging and long-term cycling. Meanwhile, a more uniform electron transport state can reduce local current concentration and the resulting excessive local electrochemical reaction, which is beneficial to slow down the local corrosion rate of the positive electrode grid during high-temperature float charging; and make the formation and reduction of lead sulfate during charging and discharging more uniform, reducing the tendency of excessive concentration of lead sulfate deposition in local areas, thereby slowing down the abnormal coarsening of lead sulfate grains and improving the utilization rate of positive electrode active material and long-term capacity retention.
[0011] Ti4O7 conductive ceramic powder possesses stable conductivity and strong corrosion resistance, maintaining a relatively stable structural state and conductivity even under high oxidation potential at the positive electrode and in sulfuric acid electrolyte environments. As Ti4O7 is a high-temperature resistant non-carbon conductive phase, compared to carbon-based conductive materials such as carbon black and graphite, it is less prone to oxidation failure under long-term high-temperature and high-potential conditions. Therefore, it can serve as a long-term stable electron transport enhancement phase within the positive electrode active material, further improving the electron transport path between active material particles. During long-term high-temperature float charging and charge-discharge processes, the positive electrode active material undergoes phase transformation, volume changes, and particle rearrangement. Ti4O7, with its high structural and conductive stability, can maintain relatively stable electron transport capabilities after the active material structure changes, reducing polarization accumulation and local electrochemical state deterioration caused by conductive structure decay during long-term cycling. This slows down the accelerated corrosion of the positive electrode grid caused by long-term high-temperature float charging and reduces the continuous deterioration of the active material structure and capacity decay. Meanwhile, Ti4O7 and antimony-doped tin dioxide form a complementary conductivity regulation effect. Antimony-doped tin dioxide mainly improves the uniformity of electron transport at the particle size of the active material, while Ti4O7 mainly improves the ability of the conductive structure to maintain its conductivity under long-term high temperature and high oxidation potential environment. The combined effect of the two helps to reduce the decay of the conductivity of the positive electrode active material with long-term cycling.
[0012] Preferably, the lead powder has a PbO content of 70%-78%.
[0013] PbO is a crucial reactive component in the formation of basic lead sulfate during the curing and aging process of cathode lead paste. Its content influences the formation of lead sulfate and basic lead sulfate crystal phases, as well as subsequent crystal growth. Higher PbO content enhances the reactivity of lead powder during paste preparation and aging, allowing PbO to react fully with sulfuric acid to form an appropriate amount of basic lead sulfate, providing a reaction basis for the formation of tetrabasic lead sulfate crystal phases. When the PbO content in lead powder is controlled within the range of 70%-78%, the added tetrabasic lead sulfate precursor can fully exert its crystal structure induction effect, making it easier to form a tetrabasic lead sulfate crystal structure with a more uniform particle size distribution and a more stable structure. This structure facilitates the formation of a stable lead dioxide active material network during formation, improving the structural stability of the cathode active material layer and reducing softening, pulverization, and shedding of the active material during cycling.
[0014] Preferably, the antimony content in the antimony-doped tin dioxide is 6%-8%.
[0015] Within this doping ratio range, antimony can stably enter the tin dioxide lattice, forming effective electron carrier centers and improving the material's electronic conductivity while maintaining the stability of the oxide crystal structure. This results in good chemical stability of antimony-doped tin dioxide in high-temperature sulfuric acid electrolyte environments. Excessive antimony content leads to increased lattice defects and decreased local crystal structure stability, reducing the material's ability to maintain its structure in long-term high-temperature acidic environments, thus causing a decline in conductivity. When the antimony content is too low, the effective carrier concentration in the lattice is insufficient, leading to reduced electronic conductivity and making it difficult to fully exert its enhancing effect on the conductive network of the positive electrode active material.
[0016] Preferably, the particle size of the Ti4O7 conductive ceramic powder is 50-150 nm.
[0017] Preferably, the mass ratio of tetrabasic lead sulfate to barium sulfate in the sulfate is 4:1 to 10:1.
[0018] Preferably, the mass ratio of organic small molecule short fibers to high silica-oxygen short chopped fibers in the short fibers is 1:1 to 3:1.
[0019] More preferably, the organic small molecule short fiber includes one of polyacrylonitrile fiber or polytetrafluoroethylene fiber.
[0020] More preferably, the organic small molecule short fiber has a length of 0.3-1.5 mm and a diameter of 5-20 μm.
[0021] More preferably, the length of the high-silica short-cut fiber is 0.2-1.0 mm and the diameter is 3-10 μm.
[0022] A second aspect of this invention provides a method for preparing positive electrode lead paste for a high-temperature resistant, long-life lead-acid battery, comprising the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate, then add lead powder and short fibers, mix evenly to obtain dry mixture; S2. Add some deionized water to the dry mixture and mix evenly to obtain a wetted mixture. S3. Mix sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0023] Preferably, the premixing time is 2-3 minutes and the premixing speed is 100-150 rpm.
[0024] Preferably, the portion of deionized water is 50%-60% of the total mass of deionized water.
[0025] A third aspect of the present invention provides a positive electrode plate for a high-temperature resistant, long-life lead-acid battery, comprising positive electrode lead paste for the high-temperature resistant, long-life lead-acid battery.
[0026] A fourth aspect of this invention provides a method for preparing a high-temperature resistant, long-life lead-acid battery positive electrode plate, comprising the following steps: The positive electrode paste of the high-temperature resistant long-life lead-acid battery is coated onto the positive electrode plate, cured and dried to obtain the positive electrode plate of the high-temperature resistant long-life lead-acid battery.
[0027] Preferably, the coating thickness is 1.2~1.5mm.
[0028] Preferably, the curing and drying temperature is 45-55°C, and the curing and drying time is 48-52 hours.
[0029] In summary, this invention effectively solves the problem of lifespan degradation in existing lead-acid batteries under high-temperature float charging conditions caused by significantly accelerated positive grid corrosion and softening and shedding of active materials, through the addition of sulfate, antimony-doped tin dioxide, and Ti4O7 conductive ceramic powder to the positive electrode lead paste. Furthermore, the initial capacity, internal resistance, and cycle consistency of the battery are not negatively affected, significantly improving the float charging cycle life and reliability of lead-acid batteries under high-temperature conditions. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] The lead powder used in the following examples and comparative examples had a PbO content of 72.8%; The antimony content in the antimony-doped tin dioxide is 7.6%; The particle size of the Ti4O7 conductive ceramic powder is 120 nm.
[0032] Example 1 This embodiment provides a positive electrode paste for a high-temperature resistant, long-life lead-acid battery, specifically including the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 10g sulfuric acid, 2.5g sulfate, 0.06g short fibers, 0.3g antimony-doped tin dioxide, 0.2g Ti4O7 conductive ceramic powder, and 11g deionized water; wherein the sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 6:1; the short fibers comprise organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 1:1, the organic small molecule short fibers have a length of 0.5mm and a diameter of 10μm, and the high-silica short-cut fibers have a length of 0.5mm and a diameter of 6μm.
[0033] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate for 2 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0034] S2. Slowly add 6g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0035] S3. Mix 10g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0036] Example 2 This embodiment provides a positive electrode paste for a high-temperature resistant, long-life lead-acid battery, specifically including the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 11g sulfuric acid, 2.8g sulfate, 0.08g short fibers, 0.2g antimony-doped tin dioxide, 0.3g Ti4O7 conductive ceramic powder, and 13g deionized water; wherein the sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 6:1; the short fibers comprise organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 2:1, the organic small molecule short fibers have a length of 0.6mm and a diameter of 10μm, and the high-silica short-cut fibers have a length of 0.3mm and a diameter of 5μm.
[0037] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate for 2 minutes at 120 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0038] S2. Slowly add 7g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0039] S3. Mix 11g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0040] Example 3 This embodiment provides a positive electrode paste for a high-temperature resistant, long-life lead-acid battery, specifically including the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 9g sulfuric acid, 3g sulfate, 0.1g short fibers, 0.4g antimony-doped tin dioxide, 0.2g Ti4O7 conductive ceramic powder, and 12g deionized water; wherein the sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 4:1; the short fibers comprise organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 1:1, the organic small molecule short fibers have a length of 1.2mm and a diameter of 5μm, and the high-silica short-cut fibers have a length of 1.0mm and a diameter of 4μm.
[0041] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate for 3 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0042] S2. Slowly add 6.5g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0043] S3. Mix 9g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0044] Example 4 This embodiment provides a positive electrode paste for a high-temperature resistant, long-life lead-acid battery, specifically including the following: The positive electrode lead paste comprises, by weight: 110g lead powder, 12g sulfuric acid, 3.5g sulfate, 0.05g short fibers, 0.2g antimony-doped tin dioxide, 0.1g Ti4O7 conductive ceramic powder, and 12g deionized water; wherein the sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 10:1; the short fibers comprise organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 3:1, the organic small molecule short fibers have a length of 0.5mm and a diameter of 8μm, and the high-silica short-cut fibers have a length of 0.3mm and a diameter of 7μm.
[0045] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate for 3 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0046] S2. Slowly add 6.7g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0047] S3. Mix 12g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0048] Comparative Example 1 This comparative example provides a positive electrode paste for a lead-acid battery. The difference from Example 1 is that the sulfate used is only tetrabasic lead sulfate; other components and processes remain unchanged. Specifically, it includes the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 10g sulfuric acid, 2.5g tetrabasic lead sulfate, 0.06g short fibers, 0.3g antimony-doped tin dioxide, 0.2g Ti4O7 conductive ceramic powder, and 11g deionized water; wherein the short fibers include organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 1:1, the organic small molecule short fibers have a length of 0.5mm and a diameter of 10μm, and the high-silica short-cut fibers have a length of 0.5mm and a diameter of 6μm.
[0049] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and tetrabasic lead sulfate for 2 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0050] S2. Slowly add 6g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0051] S3. Mix 10g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0052] Comparative Example 2 This comparative example provides a positive electrode paste for a lead-acid battery. The difference from Example 1 is that the sulfate used is only barium sulfate; other components and processes remain unchanged. Specifically, it includes the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 10g sulfuric acid, 2.5g barium sulfate, 0.06g short fibers, 0.3g antimony-doped tin dioxide, 0.2g Ti4O7 conductive ceramic powder, and 11g deionized water; wherein the short fibers include organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 1:1, the organic small molecule short fibers have a length of 0.5mm and a diameter of 10μm, and the high-silica short-cut fibers have a length of 0.5mm and a diameter of 6μm.
[0053] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and barium sulfate for 2 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0054] S2. Slowly add 6g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0055] S3. Mix 10g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0056] Comparative Example 3 This comparative example provides a positive electrode paste for a lead-acid battery. The difference from Example 1 is that antimony-doped tin dioxide is replaced with antimony trioxide, while other components and processes remain unchanged. Specifically, it includes the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 10g sulfuric acid, 2.5g sulfate, 0.06g short fibers, 0.3g antimony trioxide, 0.2g Ti4O7 conductive ceramic powder, and 11g deionized water; wherein the sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 6:1; the short fibers comprise organic small molecule short fibers and high-silica short-cut fibers in a mass ratio of 1:1, the organic small molecule short fibers have a length of 0.5mm and a diameter of 10μm, and the high-silica short-cut fibers have a length of 0.5mm and a diameter of 6μm.
[0057] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony trioxide and sulfate for 2 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0058] S2. Slowly add 6g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0059] S3. Mix 10g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0060] Comparative Example 4 This comparative example provides a positive electrode paste for a lead-acid battery. The difference from Example 1 is that the Ti4O7 conductive ceramic powder is replaced with carbon black. Other components and processes remain unchanged and will not be described in detail here. Specifically, it includes the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 10g sulfuric acid, 2.5g sulfate, 0.06g short fibers, 0.3g antimony-doped tin dioxide, 0.2g carbon black, and 11g deionized water. The sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 6:1. The organic small molecule short fibers have a length of 0.5mm and a diameter of 10μm, and the high-silica short-cut fibers have a length of 0.5mm and a diameter of 6μm in a mass ratio of 6:1. The short fibers include organic small molecule short fibers and high-silica short-cut fibers.
[0061] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix carbon black, antimony-doped tin dioxide and sulfate for 2 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0062] S2. Slowly add 6g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0063] S3. Mix 10g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0064] Comparative Example 5 This comparative example provides a positive electrode paste for a lead-acid battery. The difference from Example 1 is that the high-silica short-cut fibers are replaced with glass fibers. Other components and processes remain unchanged and will not be described in detail here. Specifically, it includes the following: The positive electrode lead paste comprises, by weight: 100g lead powder, 10g sulfuric acid, 2.5g sulfate, 0.06g short fibers, 0.3g antimony-doped tin dioxide, 0.2g Ti4O7 conductive ceramic powder, and 11g deionized water; wherein the sulfate comprises tetrabasic lead sulfate and barium sulfate in a mass ratio of 6:1; the short fibers comprise organic small molecule short fibers and glass fibers in a mass ratio of 1:1, the organic small molecule short fibers are 0.5mm long and 10μm in diameter, and the glass fibers are 0.5mm long and 6μm in diameter.
[0065] The preparation method of the positive electrode lead paste includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate for 2 minutes at 100 rpm, then add lead powder and short fibers and mix evenly to obtain a dry mixture.
[0066] S2. Slowly add 6g of deionized water to the dry mixture and mix evenly to obtain a wetted mixture.
[0067] S3. Mix 10g of sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
[0068] Application examples The positive electrode lead pastes obtained in the various embodiments and comparative examples of this application are used to prepare positive electrode plates, specifically including the following: The positive electrode paste of the high-temperature resistant long-life lead-acid battery is coated onto the positive electrode plate with a thickness of 1.3 mm. It is then cured and dried at 50°C for 50 hours to obtain the positive electrode plate of the high-temperature resistant long-life lead-acid battery.
[0069] The positive plates obtained from each application example were assembled with electrolyte and negative plates produced in the same batch to form finished lead-acid batteries, and the performance of the assembled lead-acid batteries was tested.
[0070] According to GB / T 7403.1-2018 standard, the 120A discharge capacity (Ah), the percentage of discharge capacity to rated capacity (%), the 600A discharge time (min), and the average internal resistance of the battery (mΩ) were tested respectively. The comparison results are shown in Table 1.
[0071] Table 1 Battery Performance Comparison Compared with the comparative example, the lead-acid battery of the present invention shows significant improvements in 120A discharge capacity, the percentage of discharge capacity to rated capacity, and 600A discharge time, and a significant decrease in internal resistance. This indicates that the positive electrode paste provided by the present invention does not adversely affect the initial capacity and initial internal resistance of the battery; on the contrary, it makes the battery exhibit superior performance and has good process compatibility.
[0072] Cycle life test method: In a 65℃ environment, charge at a constant voltage of 14.1 and a current limit of 75A for 16 hours, then discharge at a constant current of 50A until the termination voltage of 11.0 is considered as one cycle. When the measured discharge capacity of the entire battery pack is lower than 80% of the rated capacity, it is judged that the life has ended.
[0073] High-temperature float charge life test method: The battery is continuously float charged at 65℃±2℃ for 30 days. Then, the battery is removed and subjected to a 3-hour rate discharge test at 25℃±2℃, constituting one cycle. The test ends when the battery capacity is lower than 80% of the rated capacity at the 3-hour rate. Test results are shown in Table 2.
[0074] Table 2 Comparison of high-temperature float charging life As can be seen from Table 2, the lead-acid battery using the lead paste provided by this invention has significantly improved cycle life and high-temperature float charge life under high-temperature conditions.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A positive electrode paste for a high-temperature resistant, long-life lead-acid battery, characterized in that: The positive electrode lead paste comprises, by weight: 90-120 parts lead powder, 8-12 parts sulfuric acid, 2-3.5 parts sulfate, 0.05-0.1 parts short fibers, 0.2-0.4 parts antimony-doped tin dioxide, 0.1-0.3 parts Ti4O7 conductive ceramic powder, and 9-13 parts deionized water; wherein the sulfate includes tetrabasic lead sulfate and barium sulfate; and the short fibers include organic small molecule short fibers and high-silica short-cut fibers.
2. The positive electrode paste for a high-temperature resistant, long-life lead-acid battery as described in claim 1, characterized in that: The lead powder has a PbO content of 70%-78%; The antimony content in the antimony-doped tin dioxide is 6%-8%; The particle size of the Ti4O7 conductive ceramic powder is 50-150 nm.
3. The positive electrode paste for a high-temperature resistant, long-life lead-acid battery as described in claim 1, characterized in that: The mass ratio of tetrabasic lead sulfate to barium sulfate in the sulfate is 4:1-10:1; The mass ratio of organic small molecule short fibers to high silica-oxygen short chopped fibers in the short fibers is 1:1-3:
1.
4. The positive electrode paste for a high-temperature resistant, long-life lead-acid battery as described in claim 3, characterized in that: The organic small molecule short fibers include either polyacrylonitrile fibers or polytetrafluoroethylene fibers; The organic small molecule short fibers have a length of 0.3-1.5 mm and a diameter of 5-20 μm; The high-silica short-cut fibers have a length of 0.2-1.0 mm and a diameter of 3-10 μm.
5. The method for preparing the positive electrode lead paste for a high-temperature resistant, long-life lead-acid battery as described in claim 1, characterized in that: Includes the following steps: S1. Premix Ti4O7 conductive ceramic powder, antimony-doped tin dioxide and sulfate, then add lead powder and short fibers, mix evenly to obtain dry mixture; S2. Add some deionized water to the dry mixture and mix evenly to obtain a wetted mixture. S3. Mix sulfuric acid and the remaining deionized water evenly to obtain a sulfuric acid solution; add the sulfuric acid solution to the wetted mixture and mix evenly to obtain a positive electrode paste for a high-temperature resistant, long-life lead-acid battery.
6. The method for preparing the positive electrode lead paste for a high-temperature resistant, long-life lead-acid battery as described in claim 5, characterized in that: In S1, the premixing time is 2-3 minutes and the premixing speed is 100-150 rpm.
7. The method for preparing the positive electrode lead paste for a high-temperature resistant, long-life lead-acid battery as described in claim 5, characterized in that: In S2, the portion of deionized water is 50%-60% of the total mass of deionized water.
8. A high-temperature resistant, long-life lead-acid battery positive plate, characterized in that: This includes the positive electrode lead paste for the high-temperature resistant, long-life lead-acid battery.
9. The method for preparing the high-temperature resistant, long-life lead-acid battery positive plate as described in claim 8, characterized in that: Includes the following steps: The positive electrode paste of the high-temperature resistant long-life lead-acid battery is coated onto the positive electrode plate, cured and dried to obtain the positive electrode plate of the high-temperature resistant long-life lead-acid battery.
10. The method for preparing the high-temperature resistant, long-life lead-acid battery positive electrode plate as described in claim 9, characterized in that: The coating thickness is 1.2~1.5mm; The curing and drying temperature is 45-55℃, and the curing and drying time is 48-52 hours.